TRIE TREE ALGORITHM WITH MODIFIED KEY SAMPLINGFUNCTION - Rashid, Taghrid (Iraqi Journal of Science, 2024)
The ongoing changes in computer performance are affecting the efficiency ofstring searching algorithms. The size of main memory in typical computerscontinues to grow, but memory accesses require increasing numbers of instructioncycles.One of the most important data structure which is used to improve the stringsearching is the Trie tree.The name Trie comes from the word “retrieval”. This data structure dose not storethe data as specific elements, but rather as a path through the tree.This research aims to improve the performance of the Trie tree by using a proposedsample function in trie algorithm which improve space utilization and decrease thenumber of the search levels in the trie tree. i.e. decrease the time of searchingbecause it searches less number of levels than the standard sample function.